2020
DOI: 10.17714/gumusfenbil.630056
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Relationship between Udder Morphology, Lactation Traits and Milk Components in Morkaraman and Awassi

Abstract: In this study, it was aimed to determine the relationship between lactation traits, milk components and udder morphology in Morkaraman which accounts for approximately 21% of sheep raised in Turkey and was also used by some breeders for milk yield and Awassi sheep. 34 Morkaraman and 32 Awassi sheep were used in this study. Udder measurements were taken once in the middle lactation period (50-65 days of lactation) 2 hours before milking. Electronic caliper was used for measurements. Milk samples were taken ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
1
6
1
Order By: Relevance
“…One of the features that may be related to milk yield is different udder characteristics. In different studies conducted with different sheep breeds, it has been reported that there are relationships between some udder sizes and milk yield characteristics (Afolayan et al, 2006;Shirzeyli et al, 2013;Özyürek, 2020). In this study, the relationships between different udder sizes and marketable milk yield were investigated in Awassi sheep.…”
Section: Introductionmentioning
confidence: 87%
“…One of the features that may be related to milk yield is different udder characteristics. In different studies conducted with different sheep breeds, it has been reported that there are relationships between some udder sizes and milk yield characteristics (Afolayan et al, 2006;Shirzeyli et al, 2013;Özyürek, 2020). In this study, the relationships between different udder sizes and marketable milk yield were investigated in Awassi sheep.…”
Section: Introductionmentioning
confidence: 87%
“…In a study conducted by Kaygısız and Dağ [2] on Awassi ewes, type 1 (31%), type 2 (1%), type 3 (42%), type 4 (3%) and type 6 (23%) udders were identified. In a study conducted by Özyürek [14], 25% of the Awassi breed were found to have type 1 udder and the remaining had type 3 breasts. Similarly, type 1 and type 3 breasts were also found to be at a higher rate in this study (Table 2).…”
Section: The Scores Of Udder and Teat Linear Morphological Characteri...mentioning
confidence: 99%
“…Many studies have been conducted on the Awassi breed examining the udder and teat characteristics and the relationships between them and the milk yield in particular [1,2,7,11,12,13,14,15]. However, similar studies on Bafra sheep [9,16] are observed to be insufficient and not widespread.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Özyürek [14], it was found that 23.5% of Morkaraman and 25% of Awassi have type I udder, while the others (15.35 ± 0.23 cm), udder floor height from ground (31.88 ± 0.70 cm), teat length-right (2.85 ± 0.09 cm), teat length-left (2.76 ± 0.09 cm), teat diameter-right (1.49 ± 0.03 cm) and teat diameter-left (1.43 ± 0.04 cm) was calculated (TABLE II).…”
Section: Characteristics Of Udder and Teats In Bafra Ewes Have Been P...mentioning
confidence: 99%